Understanding maize root physiology and whole plant response to nitrogen and hormone pulse - Ishaya, Findimila Dio (2023)
Maize is widely grown for food, fodder, and biofuel. Its production requires high use of nitrogenous fertiliser for optimum productivity. But the total uptake of applied nitrogen fertiliser by cereal crops is believed to be less than 50 percent of the total amount applied. The remaining percentage constitutes environmental hazards to the environment and reduces the farmers profit margin. With this regard, several research has been conducted to address these problems, but with minimal success. It is not clear the real time depletion rate of applied nitrogen fertiliser at the background soil or adjacent to root types. Moreso, efforts to improve root uptake were faced with the challenge of how to successfully apply hormones to adults’ plants growing on soil. To solve the problem, this research aimed to determine the amount of applied nitrogen fertiliser available for uptake by maize roots, by finding the rate at which nitrate and ammonium from applied nitrogen deplete adjacent to root types and the background soil, in plants growing on low and high nitrogen background. It also aimed to determine the net uptake by maize crown and seminal roots during low and high nitrogen supply. Since the root uptake activities affects the shoot, the study examined the maize shoot response to root nitrogen dynamics during microdialysis at the short and long run. Maize has four root types which includes the primary and seminal roots (Embryonic roots), and the crown and brace roots (Post embryonic adventitious roots). The study explored the method of applying phytohormones to adult maize plants growing on soil and employed the best method to apply auxin to induce brace root emergence. Maize plants were grown in soil inside rhizobox as low and high nitrogen plants in the glasshouse. At 21 days post germination, each rhizobox was opened and sprayed with one litre of either high or low nitrogen solution. Microdialysis technique was used to sample for available nitrate and ammonium ions at the background soil and adjacent to root types, at time sequence for up to 44 hours in the longest experiment out of three experiments. The samples were analysed using the calorimetric techniques. Stable isotopes of nitrogen 15N were used to determine net influx by intact maize crown and seminal roots. PhotosynQ (Multispec), Dualex and SPAD were used to monitor shoot response to root nitrogen dynamics. Other shoot variables such as plant heights, leaf length and width for leaf area were measured weekly using tape and photographs for image analysis at the end of the experiment. Leaf numbers were counted weekly, shoots and roots fresh and dry weights were obtained at the end of each experiment. Allometric related techniques were used to obtain biomass partitioning patterns as influenced by nitrogen rates and resupply as well as the two ontogenetic phases. In order to explore the most effective method of applying hormones to adult maize plant growing on soil, gibberellins dissolved in water, and also in lanoline at 50µM and 100 µM and applied to scratched stem of maize plants. The 100 µM in water became the earliest effective means and was then used to apply auxin to stem of adult maize at 8 fully expanded leaf stage. Findings showed that ammonium rapidly disappeared from the soil surface as compared to nitrate. The occurrence was earlier during low nitrogen condition. Crown root captured more ammonium during perceived low external nitrogen while the seminal roots capture more nitrate during adequate nitrogen supply. In terms of shoot response, low nitrogen availability caused warmer canopy and enabled dissipation of excess captured solar radiation, but the quantum yield of the photosystem was not affected. The leaf area duration was higher during the onset of reproductive stage as compared to the vegetative stage while high nitrogen enabled allocation of more biomass to the stem as compared to leaves and roots in low N plants. The applied auxin enabled increased emergence of brace root whorls and number in both low and high nitrogen plants. In summary, soil nitrogen varies with space and time even in controlled environment. This affect availability of nitrogen forms for plant uptake. The concentration of nitrogen and frequency of application influence the uptake rate of nitrogen forms by different maize root types. Maize plants on low nitrogen nutrition can photosynthesise at similar rates to plants growing on adequate nitrogen supply. Auxin can be applied exogenously on adult maize growing on soil to induce the emergence of brace roots. The implication is that soil test should be carried out before fertilizer application, maize plants can be grown on low nitrogen and supplied with a dose of high N intermittently to boast uptake. The maize crown roots can be optimised for low nitrogen nutrition and the emergence of brace roots can be enhanced by auxin.